Using Home Language as a Pedagogical Resource: Working Collaboratively with Ontario Educators to Support English Language Learners in the Classroom - Paterson, Kate (Journal of the Canadian Association for Curriculum Studies, 2020)
Coherent policies to address the implications of linguistic diversity for instruction are lacking at all levels of schooling in Canada (Cummins, 2014; Volante et al., 2020). Many English language learners (ELLs)—often refugees or those of lower socioeconomic status—experience academic difficulties (Volante et al., 2017). Teachers report low self-efficacy and a lack of preparedness to meet the professional challenges of continually rising numbers of ELLs in their classrooms (Faez, 2012). Numerous studies demonstrate that students who have the opportunity to maintain and develop their Home Language (L1) at school outperform their peers in English-only programs, achieve better academic outcomes, and experience lower drop-out rates (Baker, 2011; Genesee et al., 2006; Thomas & Collier, 2002). This is because the academic language and literacy skills that students acquire in their L1 readily transfer to English (Cummins, 2017). Additionally, when L1 is validated as a valuable resource for learning, students experience an affirmation of self that contributes to positive identity formation. By joining forces with educators in collaborative professional learning teams, this study connects what we know (an extensive knowledge base that argues that the use of students’ L1 is essential to their success) and what we do (instructional practice that predominantly excludes students’ L1) in the classroom. It asks: in what ways and to what extent can collaborative professional development assist educators in providing more equitable educational opportunities for English language learners in Ontario schools?